Fungi as a toolbox for sustainable bioremediation of pesticides in soil and water. (4th May 2018) - Spina, F.; Cecchi, G.; Landinez-Torres, A.; Pecoraro, L.; Russo, F.; Wu, B.; Cai, L.; Liu, X. Z.; Tosi, S.; Varese, G. C.; Zotti, M.; Persiani, A. M.
Abstract: Pesticides can help reduce yield losses caused by pests, pathogens, and weeds, but their overuse causes serious environmental pollution. They are persistent in the environment and are biomagnified through the food chain, becoming a serious health hazard for humankind. Bioremediation, where microbes are used to degrade pesticides in situ, is a useful technology. This review summarizes data on the fungi involved in the biodegradation of chemical pesticides and their application in soil and water bioremediation. Indications for future studies in this field are given.